Soft category theory -an introduction - S. K. Sardar; Sugato Gupta (Journal of Hyperstructures)
The soft category theory offers a way to study soft theories developed so far more generally. The main purpose of this paper is to introduce the basic notions of the theory of soft categories, to present some introductory results of the theory. Also we compare soft category with fuzzy category.